Tingkat Pengetahuan Strategi dan Taktik dalam Bermain Sepak Bola Siswa Peserta Ekstrakurikuler Sepak Bola di SMP Negeri 1 Puring Kebumen 2020 - Irawan, Yogi Ferdy (Jurnal Kridatama Sains dan Teknologi, 2022)
This research is motivated by the lack of training given to strategies and tactics in playing football. This study aims to determine the level of knowledge of football extracurricular participants in SMP Negeri 1 Puring Kebumen about strategies and tactics in playing football. Research design is a quantitative descriptive. The method used is a survey method. The subjects of this study were all football extracurricular participants at SMP Negeri 1 Puring Kebumen, totaling 30 students. The instrument used was a questionnaire. The analysis technique used is to change frequency into a percentage. The results of this study indicate that the level of student knowledge of football extracurricular participants in SMP Negeri 1 Puring Kebumen on strategy in football games is 17% high category, 63% medium category, and 20% low category. Whereas the tactics in the game of football are 10% the high category, 20% the medium category, and 70% the low category. Keywords: knowledge, strategy, tactics, extracurricular, football